2009
DOI: 10.1017/s1068280500009618
|View full text |Cite
|
Sign up to set email alerts
|

Product Differentiation and Market Segmentation in Applesauce: Using a Choice Experiment to Assess the Value of Organic, Local, and Nutrition Attributes

Abstract: Recently, there has been much interest among horticultural producers concerning the marketing of organic and locally produced food. A consumer survey was administered that asked respondents to choose an applesauce product from a list of products differentiated by price, and by labels that described fat content, nutrition content, and whether the product was grown organically and/or locally. Our analysis indicates that consumers were willing to pay more for locally grown applesauce compared to applesauce that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 20 publications
5
78
1
7
Order By: Relevance
“…This finding differs from the ones by Loureiro & Hine (2002) and Pouta et al (2010) who found that consumers' WTP for the origin of production was higher than for the method of production for USA and Finnish consumers and for potatoes and poultry, respectively. However, there is substantial evidence that the importance of the method of production and origin of production depends on the consumer segment and on the analyzed products (Scarpa et al, 2005(Scarpa et al, , 2007aHu et al, 2009;James et al, 2009;Yue & Tong, 2009;Wolf et al, 2011). Our results reinforce the notion that the relative importance attached by consumers to the method and origin of production attributes when shopping depends on the specific product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding differs from the ones by Loureiro & Hine (2002) and Pouta et al (2010) who found that consumers' WTP for the origin of production was higher than for the method of production for USA and Finnish consumers and for potatoes and poultry, respectively. However, there is substantial evidence that the importance of the method of production and origin of production depends on the consumer segment and on the analyzed products (Scarpa et al, 2005(Scarpa et al, , 2007aHu et al, 2009;James et al, 2009;Yue & Tong, 2009;Wolf et al, 2011). Our results reinforce the notion that the relative importance attached by consumers to the method and origin of production attributes when shopping depends on the specific product.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several empirical papers analyzed preferences for both attributes, method of production and origin of production (Loureiro & Hine, 2002;Scarpa et al, 2005Scarpa et al, , 2007aHu et al, 2009;James et al, 2009;Yue & Tong, 2009;Pouta et al, 2010;Wolf et al, 2011;Hu et al, 2012) using different levels for both attributes 6 . These studies used a choice experiment to assess consumers' willingness to pay (WTP) for different products (potatoes, oranges, grapes, olive oil, poultry, tomatoes, carrots, applesauce, blueberry products and milk) in USA and Europe (Finland and Italy).…”
mentioning
confidence: 99%
“…For instance, Rao and Monroe (1988) suggested that the variations in rural consumers' preferences and WTP were due to gaps in their respective incomes, rather than their prior knowledge (or lack thereof) of the products. Two studies by Dentoni, Tonsor, Calantone, and Peterson (2009) and by James, Rickard, and Rossman (2009) suggested that consumers who have better knowledge of a product actually had less preference and WTP for that product's credibility attributes. Yu and Gao (2010) suggested that variations in study methods, the selection of product and consumer attributes, the study time period, and the geographic locations all contributed to the inconsistency of estimating WTP for beef cuts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a product's "organic" designation does not necessarily ensure a stable profit margin. For instance, James et al (2009) applied the stated choice method in a survey study and found that a better knowledge of agricultural production would actually reduce consumers' WTP for organic products. Furthermore, the stiff market competition associated with the organic food industry has created obstacles for local producers to start up a business in organic production.…”
Section: Attribute Selectionmentioning
confidence: 99%
“…Pasar memperlakukan suatu komoditas secara ekivalen tanpa mempedulikan siapa yang memproduksi komoditas tersebut. Citra yang melekat pada diferensiasi produk memiliki kapasitas untuk menghela keputusan pembelian konsumen secara positif dan sekaligus mengamankan sumber keunggulan kompetitif produk bersangkutan (Kim dan Boyd 2004, James et al 2009). Diferensiasi produk berhubungan erat dengan segmentasi pasar dan secara konsisten mendeskripsikan strategi pemasaran niche.…”
unclassified